Genetic counselling and testing of susceptibility genes for therapeutic decision-making in breast cancer—an European consensus statement and expert recommendations. (January 2019) - Singer, Christian F.; Balmaña, Judith; Bürki, Nicole; Delaloge, Suzette; Filieri, Maria Elisabetta; Gerdes, Anna-Marie; Grindedal, Eli Marie; Han, Sileni; Johansson, Oskar; Kaufman, Bella; Krajc, Mateja; Loman, Niklas; et al.
Abstract: An international panel of experts representing 17 European countries and Israel convened to discuss current needs and future developments in BRCA testing and counselling and to issue consensus recommendations. The experts agreed that, with the increasing availability of high-throughput testing platforms and the registration of poly-ADP-ribose-polymerase inhibitors, the need for genetic counselling and testing will rapidly increase in the near future. Consequently, the already existing shortage of genetic counsellors is expected to worsen and to compromise the quality of care particularly in individuals and families with suspected or proven hereditary breast or ovarian cancer. Increasing educational efforts within the breast cancer caregiver community may alleviate this limitation by enabling all involved specialities to perform genetic counselling. In the therapeutic setting, for patients with a clinical suspicion of genetic susceptibility and if the results may have an immediate impact on the therapeutic strategy, the majority voted that BRCA1/2 testing should be performed after histological diagnosis of breast cancer, regardless of oestrogen receptor and human epidermal growth factor receptor 2 (HER2) status. Experts also agreed that, in the predictive and therapeutic setting, genetic testing should be limited to individuals with a personal or family history suggestive of a BRCA1/2 pathogenic variant and should also include high-risk actionable genes beyond BRCA1/2 . Of high-risk actionable genes, all pathological variants (i.e. class IV and V) should be reported; class III variants of unknown significance, should be reported provided that the current lack of clinical utility of the variant is expressly stated. Genetic counselling should always address the possibility that already tested individuals might be re-contacted in case new information on a particular variant results in a re-classification.